Anatomy of the Italian occupational structure: Concentrated power and distributed knowledge - Armanda Cetrulo; Dario Guarascio; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Which type of work do Italians perform? In this contribution we aim at detecting the anatomy of the Italian occupational structure by taking stock of a micro-level dataset registering the task content, the execution of procedures, the knowledge embedded in the work itself, called ICP (Indagine Campionaria sulle Professioni), the latter being comparable to the U.S. O*NET dataset. We perform an extensive empirical investigation moving from the micro to the macro level of aggregation. Our results show that the Italian occupational structure is strongly hierarchical, with the locus of power distinct by the locus of knowledge generation. It is also weak in terms of collaborative and worker involvement practices, and possibility to be creative. Our analysis allows to pinpoint the role exerted by hierarchical structures, decision making autonomy, and knowledge as the most relevant attributes characterizing the division of labour.
Keywords: J2; D2; C38; 330; Occupational structure; power; knowledge; factor analysis